EVALUATION OF TECHNICAL PARAMETERS LOCOMOTIVE FOR RAILWAY CAREER TRANSPORT (Transport systems and technologies, 2022)
The main technical parameters of the locomotive for quarry railway transport have been evaluated. The design parameters of the locomotive have been determined and it is established that the tangential power is 6700 kW, and the traction force for the design mode is 1300 kN. The calculations of the traction characteristics of the locomotive have been performed. The procedure for determining the parameters of the locomotive operating modes during train tasks performing has been proposed, which is based on the processing of the results of traction task solving on the section of the track. It has been established that for the test section of the track a significant part of the time in the traction mode the locomotive operates with a load of 10… 25% of the nominal, therefore it has been proposed to implement the mode of movement with disconnection of traction motors. The use of an onboard energy storage system, which allows the accumulation of energy during electrodynamics braking has been proposed. The generalized scheme of traction system which allows realizing ways of increase of energy efficiency a rolling stock has been offered.
Keywords: locomotive, traction force, traction electric drive, energy efficiency.